The Effect of Special Exercises Using Aiding Devices on Developing Agility and Coordination in 3×3 female basketball players U18 - Habeeb, Doaa; Abd Alsatar, Muhanad (Journal of Physical Education, 2020)
The research aimed at designing special exercises using aiding devices for developing agility and coordination in 3×3 female basketball players U18 of Zema sport club as well as identifying the effect of these exercises on developing agility and coordination in basketball players. The researchers used the experimental method on (6) basketball players in each group. The researcher applied the experiment using aiding devices and (4) training sessions for eight weeks. The results showed a significant effect on the agility and coordination test in both groups in favor of the experimental group.